What makes a compliant Phase III and pre-launch patient advocacy strategy?. Issue 1 (1st January 2016) - Hicks, Nick; Allan, Keith; Thalheim, Christoph; Woods, Paul
Abstract : Background: A key task for the pharmaceutical industry is to understand the compliance implications of engaging with a patient advocacy group (PAG). This presents challenges for the industry to negotiate the ethical and reputational issues that can arise when working with a PAG. Objective: To gain the views of pharmaceutical industry executives on future compliance challenges when working with PAGs. Study design: We conducted two surveys among two sets of industry executives: one group focussed on market access roles and the other focussed on non-market access roles. Results: Transparency was identified as the biggest challenge, followed by project rationale and then by project ownership. Conclusion: We explore how this can be overcome and make recommendations on how best to work compliantly with PAGs.